Somatic Embryogenesis of Pinus sylvestris L. from Parent Genotypes with High- and Low Stilbene Content in Their Heartwood - Harju, Anni; Heiska, Susanne; Julkunen-Tiitto, Riitta; Venäläinen, Martti; Aronen, Tuija (MDPI AG, 2022)
The increasing concern about ecological impacts of wood preservation chemicals has raised the interest in the natural durability of Scots pine (Pinus sylvestris L.) heartwood. Phenolic compounds—stilbenes—have been found to inhibit fungal growth, making heartwood more resistant to decay. There is a strong genetic component in the stilbene content of the heartwood in Scots pine, with a positive correlation between stilbene content in the heartwood of mother trees and their progenies. Vegetative propagation, i.e., somatic embryogenesis (SE) of Scots pine genotypes with high content of stilbenes could provide a way to produce more durable timber, assuming that there is no trade-off between SE propagation and capacity for high stilbene synthesis. To study this, we made SE initiations from parent genotypes with high and low content of stilbenes in their heartwood, using seed embryos from both open-pollinations and controlled crossings as explants. The success of SE was followed from initiation to embling acclimatization, together with measurements of stilbene content in the explants and the established SE lines. The results show that SE can be induced and emblings regenerated from trees with both high and low content of stilbene. Content of stilbenes was generally low in SE cultures and varied widely among the lines. Following the successful initiation, the later phases of SE propagation proceeded with no connection to the parent genotypes or the stilbene level of the ECs and had large variation among SE-lines.
Keywords: varhaisvalinta; uuteaineet; lahonkestävyys; runkopuu; metsänjalostus; in vitro -menetelmä; puunlaatuominaisuus; kasvullinen lisäys; early selection; extractives; decay resistance; stem-wood; tree breeding; in vitro; timber quality; vegetative propagation